2017
DOI: 10.1155/2017/3525349
|View full text |Cite
|
Sign up to set email alerts
|

Severity, Treatment, and Outcome of Acute Pancreatitis in Thailand: The First Comprehensive Review Using Revised Atlanta Classification

Abstract: Background. Severity and outcome of acute pancreatitis (AP) in Thailand are unknown. Methods. A retrospective study of 250 patients with AP during 2011–2014 was performed. Severity, treatment, and outcome were evaluated. Severity was classified by revised Atlanta classification. Results. The mean age was 58 years and 56% were men. Etiologies were gallstones (45%), alcohol (16%), postendoscopic retrograde cholangiopancreatography (14%), and idiopathic (15%). Overall, 72%, 16%, and 12% of patients had mild, mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(45 reference statements)
4
15
0
1
Order By: Relevance
“…As per Bidarkundi et al the main etiology was alcoholism (46.67%), while Singh et al, Papachristou et al and pongprasobchai et al found gall stone disease to be the main etiological factor with 27%, 36% and 45% respectively. 1,[11][12][13] In present study, nine patients out of 14 with BISAP score more than or equal to three had severe AP and the values are statistically significant p value <0.01. In the studies by Singh et On depicting sensitivity and specificity of BISAP score and APACHE II score for severity in ROC curve, the best cut-off point is obtained at 3 and 10 respectively.…”
Section: Discussionsupporting
confidence: 49%
“…As per Bidarkundi et al the main etiology was alcoholism (46.67%), while Singh et al, Papachristou et al and pongprasobchai et al found gall stone disease to be the main etiological factor with 27%, 36% and 45% respectively. 1,[11][12][13] In present study, nine patients out of 14 with BISAP score more than or equal to three had severe AP and the values are statistically significant p value <0.01. In the studies by Singh et On depicting sensitivity and specificity of BISAP score and APACHE II score for severity in ROC curve, the best cut-off point is obtained at 3 and 10 respectively.…”
Section: Discussionsupporting
confidence: 49%
“…For the Asia subgroup, 9 studies were selected 9,12,27,33,37,39,49,50,52 from China, India, Taiwan, Oman, Korea and Thailand. One article from Australia 40 was included and represented Oceania in the combined summary effects representation (Fig.…”
Section: Hpbmentioning
confidence: 99%
“…Other causes of AP Forty-one articles [8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52] assessed other less frequent aetiologies of AP and are summarized in Supplementary Table 2. These miscellaneous causes were responsible for 2-29% of the presentations with AP.…”
Section: Hpbmentioning
confidence: 99%
“…Among the radiological studies, CT with contrast is the most prevalent modality used for disease staging and for determining severity. It is used in evaluation of the pancreatic parenchyma and detecting pancreatic and extra pancreatic inflammation, which is closely linked to the severity of the course of the disease [3]. However, CT cannot be used in patients who have contraindications for iodinated contrast media, as it has been found to aggravate the disease and worsen the renal failure often caused by acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%